Light-induced insulator-metal transition in Sr2IrO4 reveals the nature of the insulating ground state - Choi, Dongsung; Yue, Changming; Azoury, Doron; Porter, Zachary; Chen, Jiyu; Petocchi, Francesco; Baldini, Edoardo; Lv, Baiqing; Mogi, Masataka; Su, Yifan; Wilson, Stephen D.; Eckstein, Martin; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Sr2IrO4 has attracted considerable attention due to its structural and electronic similarities to La2CuO4, the parent compound of high-Tc superconducting cuprates. It was proposed as a strong spin-orbit-coupled Jeff = 1/2 Mott insulator, but the Mott nature of its insulating ground state has not been conclusively established. Here, we use ultrafast laser pulses to realize an insulator-metal transition in Sr2IrO4 and probe the resulting dynamics using time- and angle-resolved photoemission spectroscopy. We observe a gap closure and the formation of weakly renormalized electronic bands in the gap region. Comparing these observations to the expected temperature and doping evolution of Mott gaps and Hubbard bands provides clear evidence that the insulating state does not originate from Mott correlations. We instead propose a correlated band insulator picture, where antiferromagnetic correlations play a key role in the gap opening. More broadly, our results demonstrate that energy-momentum-resolved nonequilibrium dynamics can be used to clarify the nature of equilibrium states in correlated materials.
CRIS-Team Scopus Importer:2024-07-19
Keywords: cluster dynamical mean-field theory; correlated band insulator; light-induced insulator–metal transition; time- and angle-resolved photoemission spectroscopy